Solving discrete ordered median problems with induced order: preliminary results - Domínguez-Merino, Enrique; Marín, Alfredo (My University, 2018)
The Discrete Ordered Median Problem with Induced Order (DOMP+IO) is a multi-level version of the classical DOMP, which has been widely studied. In this work, a DOMP+IO with two types of facilites (levels) is considered and some preliminary results are provided.
Keywords: Localización, Teoría de; Ordered median problem; Indudeced ordered; Discrete location